Survival of Clostridium difficile spores at low temperatures. (April 2015) - Deng, Kai; Plaza-Garrido, Angela; Torres, J. Antonio; Paredes-Sabja, Daniel
Abstract: Clostridium difficile 's presence has been reported in meat products stored typically at low temperatures. This study evaluated the viability in phosphate buffer saline (PBS) of spores from epidemic C. difficile strain R20291 (4.6 log CFU/ml) and M120 (7.8 log CFU/ml). Viability was assessed during 4 months at −80 °C,  −20 °C, 4 °C (refrigeration), and 23 °C (room temperature), and after 10 freeze (−20 °C)/thaw (+23 °C) cycles. Although spore viability decreased, significant viability was still observed after 4 months at −20 °C, i.e., 3.5 and 3.9 log CFU/ml and −80 °C, i.e., 6.0 and 6.1 log CFU/ml for strains R20291 and M120, respectively. The same trend was observed for M120 at 4 °C and 23 °C, while for R20291 the viability change was non-significant at 4 °C but increased significantly at 23 °C ( p  > 0.05). After 10 freeze-thaw cycles, viability of both strains decreased but a significant fraction remained viable (4.3 and 6.3 log CFU/ml for strain R20291 and M120, respectively). Strikingly, both strains showed higher viability in a meat model than in PBS. A small but significant decrease ( p  < 0.05) from 6.7 to 6.3 log CFU/ml in M120 viability was observed after 2-month storage in the meat model while the decrease from an initial 3.4 log CFU/ml observed for R20291 was non-significant ( p  = 0.12). In summary, C. difficile spores can survive low-temperature conditions for up to 4 months. Highlights: Clostridium difficile spore viability significantly decreased at −20 °C and −80 °C. C. difficile spore forming ability increased after 4 month at room temperature. C. difficile spores are able to survive in meat products under frozen conditions.